Examination of Disaster and Emergency Assembly Areas and Recommendation of Potential Areas: The Case of Akçaabat Trabzon - Gülten Kara; Kadir Kaan Yavruoğlu (Doğal Afetler ve Çevre Dergisi)
Assembly areas for disaster and emergency situations are designated places where people can safely gather and meet their basic needs during critical times, such as natural disasters like earthquakes, fires, and terrorist attacks. These areas are mostly open and green spaces, easily accessible to the people. However, over time, due to population growth, unplanned urbanization, lack of maintenance, and changes in planning, these areas may become insufficient to meet the demand. Evaluating disaster and emergency assembly areas according to selected criteria plays a critical role in community safety and disaster management. Effective assessment of these assembly areas, identifying deficiencies and requirements, facilitates disaster management processes. The aim of this study is to assess the disaster and emergency assembly areas in the Akçaabat district of Trabzon in terms of accessibility, usability, multifunctionality, technical infrastructure facilities, spatial size and capacity, the height of surrounding buildings, the distance between the assembly areas and surrounding buildings, and the proximity to sea and riverbeds. The evaluation results indicated that the disaster and emergency assembly areas are generally insufficient throughout the district, and potential new assembly areas have been presented. Additionally, recommendations have been made to address the deficiencies and requirements of the disaster and emergency assembly areas in Akçaabat district.